Neuronal architecture of the antennal lobe in Drosophila melanogaster. - Stocker, R.F.; Lienhard, M.C.; Borst, A.; Fischbach, K.F. (Cell and Tissue Research, 1990)
Computer reconstruction of the antennal lobe of Drosophila melanogaster has revealed a total of 35 glomeruli, of which 30 are located in the periphery of the lobe and 5 in its center. Several prominent glomeruli are recognizable by their location, size, and shape; others are identifiable only by their positions relative to prominent glomeruli. No obvious sexual dimorphism of the glomerular architecture was observed. Golgi impregnations revealed: (1) Five of the glomeruli are exclusive targets for ipsilateral antennal input, whereas all others receive afferents from both antennae. Unilateral amputation of the third antennal segment led to a loss of about 1000 fibers in the antennal commissure. Hence, about 5/6 of the approximately 1200 antennal afferents per side have a process that extends into the contralateral lobe. (2) Afferents from maxillary palps (most likely from basiconic sensilla) project into both ipsi- and contralateral antennal lobes, yet their target glomeruli are apparently not the same as those of antennal basiconic sensilla. (3) Afferents in the antennal lobe may also stem from pharyngeal sensilla. (4) The most prominent types of interneurons with arborizations in the antennal lobe are: (i) local interneurons ramifying in the entire lobe, (ii) unilateral relay interneurons that extend from single glomeruli into the calyx and the lateral protocerebrum (LPR), (iii) unilateral interneurons that connect several glomeruli with the LPR only, (iv) bilateral interneurons that link a small number of glomeruli in both antennal lobes with the calyx and LPR, (v) giant bilateral interneurons characterized by extensive ramifications in both antennal lobes and the posterior brain and a cell body situated in the midline of the suboesophageal ganglion, and (vi) a unilateral interneuron with extensive arborization in one antennal lobe and the posterior brain and a process that extends into the thorax. These structural results are discussed in the context of the available functional and behavioral data.